The Anti-Psoriatic Efficacy and Safety Profile of Topical and Intralesional Methotrexate: A Literature Review - Chaiyabutr C; Punnakitikashem P; Silpa-archa N; Wongpraprarut C; Chularojanamontri L (Dove Medical Press, 2022)
Chayada Chaiyabutr,1 Primana Punnakitikashem,2 Narumol Silpa-archa,1 Chanisada Wongpraprarut,1 Leena Chularojanamontri1 1Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, Thailand; 2Department of Biochemistry, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Leena Chularojanamontri, Department of Dermatology, Faculty of Medicine Siriraj Hospital, Mahidol University, 2 Wanglang Road, Bangkok Noi, Bangkok, 10700, Thailand, Tel +66 2 419 4333, Fax +66 2 411 5031, Email leenajim@gmail.comAbstract: Methotrexate (MTX) has long been considered the first-line oral systemic pharmacotherapy for psoriasis. The drug has several well-known systemic side effects, such as bone marrow suppression and hepatotoxicity. To avoid them, the use of topical or intralesional administrations of MTX has become an interesting option. With the advent of novel drug delivery systems, especially nanocarriers, the usage of a high-efficacy and safe topical MTX for psoriasis has nearly been attained. This review examined the development, anti-psoriatic efficacy and adverse effects of topical forms of MTX (plain MTX; MTX with chemical enhancer; MTX using nanotechnology; MTX with protein transduction domains; MTX with liquid crystalline systems; and MTX with physical enhancer/laser) and intralesional MTX in psoriasis patients and psoriasis-induced animals. The efficacy of topical MTX varied with the drug delivery technology employed. Nevertheless, the overall safety profile of the topical forms was favourable. A 25 mg/mL MTX solution injected intralesionally at the nail matrix worked well for nail psoriasis recalcitrant to topical treatment. To improve the standard of care for patients with psoriasis, randomized controlled trials that establish the most effective MTX-delivery system are needed.Keywords: drug delivery, intralesional, liposome, methotrexate, psoriasis, topical